Natural Language Processing - Jain, Aditya; Kulkarni, Gandhar; Shah, Vraj (International Journal of Computer Sciences and Engineering, 2025)
Natural language processing is widely discussed and researched topic nowadays. As it is one of the oldest area of research in machine learning it is used in major fields such as machine translation speech recognition and text processing. Natural language processing has brought major breakthrough in the field of computation and AI. Various algorithms used for Natural language processing are mainly dependent on the recurrent neural network. Different text and speech processing algorithm are discussed in this review paper and their working is explained with examples. Results of various algorithms show the development done in this field over past decade or so. We have tried to differentiate between various algorithms and also its future scope of research. The Gap analysis between different algorithms is mentioned in the paper as well as the application of these various algorithms is also explained. Natural language processing has not attained perfection till date but continuous improvement done is the field can surely touch the perfection line. Different AI now use natural language processing algorithms to recognize and process the voice command given by user.